Exploring the Pathways Between Transformative Group Experiences and Identity Fusion - Kavanagh, Christopher M.; Kapitány, Rohan; Putra, Idhamsyah Eka; Whitehouse, Harvey (Frontiers in Psychology, 2020)
A growing body of evidence suggests that two distinct forms of group alignment are possible: identification and fusion (the former asserts that group and personal identity are distinct, while the latter asserts group and personal identities are functionally equivalent and mutually reinforcing). Among highly fused individuals, group identity taps directly into personal agency and so any attack on the group is perceived as a personal attack and motivates a willingness to fight and possibly even die as a defensive response. As such, identity fusion is relevant in explaining violent extremism, including suicidal terrorist attacks. Identity fusion is theorized to arise as a result from the sharing of personally transformative experiences with other group members, however evidence for this relationship remains limited to date. Here, we present a pre-registered study in which we examine the role of transformativeness and perceived sharedness of group-defining events in generating identity fusion. We find that both of these factors are predictive of identity fusion but that the relationship with transformativeness was more consistent than perceived sharedness across analyses in a sample of Indonesian Muslims.